PERAN SARANA DAN PRASARANA SEKOLAH DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG KONDUSIF DI MA NURUL HIDAYAH JAMBI - Giyati; Nurfadlilah Muhyi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study assesses how infrastructure and amenities at MA Nurul Hidayah in Jambi contribute to creating a favorable learning environment. Through observation, interviews, and documentation, information was gathered from the principal of the school, instructors, and students using a descriptive qualitative method. The Miles and Huberman analytical technique was then used to examine the data. Adequate facilities greatly enhance students' comfort, focus, and motivation to learn, according to the research findings. Despite the fact that procurement planning has been incorporated through the BOS-funded ERKAM system, this study found challenges due to the building's physical state and the scarcity of digital equipment. The primary suggestions for the sustainability of an optimal learning environment are to enhance the quality of technology facilities and optimize facility management. Keywords: facilities and infrastructure, learning environment, madrasah